PEMBERDAYAAN DAN PENGEMBANGAN UKM SEBAGAI PENGGERAK EKONOMI DESA. (DESA HARJOBINANGUN, PAKEM, SLEMAN, DI YOGYAKARTA) - Lutfi Chabib; Yosi Febrianti; Abdul Hakim; Muhammad Safarullah; Bambang Subekti (Asian Journal of Innovation and Entrepreneurship, 2016)
Small and medium enterprise (SME/UKM) plays an important role in the national economic development, due its role in the economic growth and employee recruitment as well as its role in the development of product distribution. During the economic crysis that occured in this country a few years ago, which affected to the collapse of many big scale firms, Small and Medium Enterprise (SME/UKM) proved tougher in facing the crisis. Small and Medium Enterprise (SME/UKM) Dharma Karya is located in Harjobinangun, Pakem, Sleman, Daerah Istimewa Yogyakarta. Small and Medium Enterprise (SME/UKM) Dharma Karya has problems which are cannot grow as much as possible due to a limitation of facilities of production process so it can’t be produce many product in maximum amount. The other problem is Small and Medium Enterprise (SME/UKM) Dharma Karya cannot sell their product in market because a limitation of skill and the product socialization. So that, KKN PPM UII is conducting a progam of procurement of required equipment and mentoring of entrepreneurship motivation, improvement of product quality, packaging products, quality of packaging, networking and cooperation. This program can improve the quality and productivity of Small and Medium Enterprise (SME/UKM) so that improve the rural economy.